LANGUAGE and CULTURE in RELATION to INTERCULTURAL COMMUNICATION in A BUSINESS CONTEXT - I. Tiono, Nani (k@ta: A Biannual Publication on the Study of Language and Literature, 2004)
Intercultural communication; that is, face-to-face communication between people from different cultural background, often has hindrances because of some factors such as the vocabulary, the discourse pattern and the concept of time. Thus, this paper will analyze how these factors can hinder the intercultural communication between the Asians and Americans and what might become the result of the intercultural miscommunication, especially in business contexts.